2006
DOI: 10.1111/j.1651-2227.2006.tb02202.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors and clinical significance of acanthosis nigricans in obese Japanese children and adolescents

Abstract: We demonstrate that AN is a useful clinical marker for the severity of obesity associated with a high BMI, and that B2ADR Gly16 and B3ADR Arg64 are associated synergistically with AN in obese children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
2
9
0
2
Order By: Relevance
“…In the present study, patients with AN had significantly higher BMI than obese control subjects without AN. This is in agreement with the results of other studies that have reported the BMI of subjects with AN to be significantly greater than that in subjects without AN …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, patients with AN had significantly higher BMI than obese control subjects without AN. This is in agreement with the results of other studies that have reported the BMI of subjects with AN to be significantly greater than that in subjects without AN …”
Section: Discussionsupporting
confidence: 93%
“…However, the correlation of serum leptin with other CVD risk factors was not studied. Similarly, Miura et al . reported that serum leptin was significantly higher in obese children and adolescents with AN than in obese control subjects.…”
Section: Discussionmentioning
confidence: 85%
“…Sendo assim, o achado de alta prevalência de fatores de risco para doença cardiovascular ateroscleró-tica, como circunferência da cintura aumentada, HDLcolesterol baixo e triglicérides altos, é preocupante. A alta prevalência de acantose nigricans, considerada marcador de resistência insulínica, mesmo em crianças (37)(38)(39)(40), também chama a atenção.…”
Section: Discussionunclassified
“…8,9 Although the rates of AN and obesity are different among races, a close association between these clinical findings and IR was documented in children from many countries and various ethnicities. 3,9,[10][11][12][13][14][15][16] The investigation of IR status requires a blood withdrawn under fasting condition and is associated with pain, patient's reluctance, and poor compliance. Thus, the clinical dermatological finding of AN may offer an easier solution to detect IR in obese children with better patient's compliance and parents acceptance.…”
Section: Introductionmentioning
confidence: 99%